2022
DOI: 10.21608/erjeng.2022.167621.1107
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Sustainable Material to Improve the Geotechnical Properties of Silty Clay – Experimental and Numerical Study

Abstract: Soil reinforcement is a modern and specialized soil improvement field. It includes a variety of procedures involving the placement of inclusions in soil. The majority of research has been conducted without respect to the fundamental features of reinforced soil on the behavior of foundations on reinforced soil. As a result, this study provides an laboratory study of the mechanical and compressibility characteristics of a specimen of reinforced silty clay at a medium depth using an environment friendly jute clot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…The ultimate bearing capacities of reinforced soils were higher than that of unreinforced soil by 45.82% for the reinforcement layer embedded at a depth equal to u/B=0.5 and 37.48% for the reinforcement layer embedded at a depth equal to u/B =1, respectively. The values were agreeable with the literature [1][2][3][4][5][6][7][8]15,16]. The bearing capacity escalation and settlement declination are due to the soil compression above the reinforcement.…”
Section: 1bearing Capacity and Settlementsupporting
confidence: 89%
See 1 more Smart Citation
“…The ultimate bearing capacities of reinforced soils were higher than that of unreinforced soil by 45.82% for the reinforcement layer embedded at a depth equal to u/B=0.5 and 37.48% for the reinforcement layer embedded at a depth equal to u/B =1, respectively. The values were agreeable with the literature [1][2][3][4][5][6][7][8]15,16]. The bearing capacity escalation and settlement declination are due to the soil compression above the reinforcement.…”
Section: 1bearing Capacity and Settlementsupporting
confidence: 89%
“…They also illustrated that the effectiveness of reinforcement extends up to a 1.4-time width for square foundations on geogrid reinforced sand. Bahloul [7] utilised the jute cloth as a geotextile for studying the geotechnical properties of silty clay. It was observed that there was a 33% and 29% increase in the angle of shear and cohesion, respectively.…”
Section: Introductionmentioning
confidence: 99%